The city of the new normality, the example of Skopje - Violeta Bakalchev; Tasic Sasha; Minas Bakalchev; Aleksandar Petanovsk (University American College Skopje, 2021)
In the period of the post-earthquake reconstruction, it was stated that Skopje should face the "new normality" of the city. Sixty years later, "new normality" is becoming a global phenomenon in the face of the effects of the ongoing worldwide pandemic of coronavirus disease. It is becoming evident that the modern world is facing a variety of crises. Hence the need for our life environment to perceive and rethink in relation to a continuous possible crisis. The city of Skopje in its recent history has faced the catastrophic earthquake of 1963 and more recently the current pandemic. Both conditions caused changes in his daily life. But what are the similarities and differences between these critical thresholds? Can they contribute to dealing with future uncertain events? In the case of the earthquake, we follow visible consequences of its physical structure, in the case of the pandemic in its health condition, socio, cultural and economic structure. But in both cases the established normality has changed. This paper will explore precisely the consequences of crisis situations and will connect them in the continuous variability of the context of the contemporary city.
Keywords: 330; new normality; city; crisis; post-earthquake recovery; post-pandemic recovery